Higher serotonin transporter availability in early‐onset obsessive–compulsive disorder patients undergoing escitalopram treatment: A [11C]DASB PET study. (6th December 2017) - Lee, Junhee; Kim, Bo‐Hyung; Kim, Euitae; Howes, Oliver D.; Cho, Kang Ik Kevin; Yoon, Youngwoo Bryan; Kwon, Jun Soo
Abstract: Objective: Early‐onset obsessive–compulsive disorder (EOCD) and late‐onset obsessive–compulsive disorder (LOCD) are distinct subtypes of obsessive–compulsive disorder (OCD). OCD patients are treated with serotonin reuptake inhibitors, but the difference in serotonin transporter (SERT) availability between medicated EOCD and LOCD is unexplored yet. Methods: Six EOCD and 6 LOCD patients were enrolled. They underwent serial [ 11 C]DASB positron emission tomography scans during maintenance therapy with escitalopram, and their plasma concentration of escitalopram was measured simultaneously with the scan. Then, the drug‐free binding potential of SERT was calculated by pharmacokinetic–pharmacodynamic modelling. Results: In comparison with LOCD patients, SERT availability was significantly higher in the putamen of EOCD patients ( U = 4, p = .026), but not in the caudate nucleus ( U = 14, p = .589), thalamus ( U = 16, p = .818), and dorsal raphe nucleus ( U = 7, p = .093). Binding potential of putamen showed a negative correlation ( r = −.580, p = .048) with age of onset of the disease, but not with the Yale–Brown Obsessive Compulsive Scale scores. Conclusions: These findings indicate that the earlier the age of onset of OCD, the less serotonergic pathology there is and that this difference remains even after long‐term serotonin reuptake inhibitor treatment. Clinically, it might suggest that nonserotonergic treatments would be a better option for EOCD patients.